The Influence of the Size, Age and Sex on the Computed Tomographic Measured Size of the Pituitary Gland in Normal Horses. (27th February 2017) - Crijns, C. P.; Van Bree, H. J.; Broeckx, B. J. G.; Schauvliege, S.; Van Loon, G.; Martens, A.; Vanderperren, K.; Dingemanse, W. B.; Gielen, I. M.
Summary: The objective of this study was to examine the influence of the size, age and sex of the horse on the size of the pituitary gland and determine the possibility of using the pituitary gland height‐to‐brain area ratio (P:B ratio) to allow comparison of different sized and aged horses. Thirty‐two horses without pituitary pars inter‐media dysfunction that underwent a contrast‐enhanced computed tomographic (CT) examination were included in a cross‐sectional study. On the CT images, the pituitary gland height was measured and the P:B ratio was calculated. These measurements were correlated to the size, age and sex of the horses. The pituitary gland height was significantly associated with the size ( P  < 0.001) and the age ( P  < 0.001), but not with the sex ( P  = 0.40), of the horses. No significant association was found between the P:B ratio and the size ( P  = 0.25), the age ( P  = 0.06) or the sex ( P  = 0.25) of the horses. In conclusion, the pituitary gland size varies between different sized and aged horses. The use of the P:B ratio is a valuable metric for making comparisons between the pituitary glands of these horses.